PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PENGGUNA JASA PENERBANGAN LOW COST CARRIERS DI INDONESIA - Winny Handayani; Fitri Novika Widjaja; Veny Megawati (CALYPTRA, 2020)
Abstract - The purpose of this research is to know the effect of service quality through dimensions tangible features, flight schedules, service provided by ground staff, service provided by flight attendant, and online services to low cost carriers’ (LCC) customer satisfaction. It was found that flight schedules and online services have a significant effect on customer satisfaction. While tangible features, the services provided by ground staff and flight attendants do not have a significant effect on customer satisfaction. This study was a replica of study by Eng et al. (2012). The results of this study showed two out f five hypotheses wereconcistent with study by Eng et al. (2012).